Human Sgo1 downregulation leads to chromosomal instability in colorectal cancer. Issue 2 (17th July 2008) - Iwaizumi, M; Shinmura, K; Mori, H; Yamada, H; Suzuki, M; Kitayama, Y; Igarashi, H; Nakamura, T; Suzuki, H; Watanabe, Y; Hishida, A; Ikuma, M; et al.
Abstract : Background and aims: Chromosomal instability (CIN) is recognised as a hallmark of cancer and is caused by a spindle assembly checkpoint disorder or chromosome mis-segregation during mitosis. Although the recent identification of human shugoshin (hSgo1), an important player in proper chromosome segregation, has suggested the involvement of hSgo1 in colorectal tumourigenesis, little is known about how it is involved. The aim of this study was to obtain information about the status of hSgo1 in human colorectal cancer. Method and results: Among the 46 colorectal cancer cases, hSgo1 mRNA expression was decreased in the tumour tissue in comparison with the corresponding normal tissue (p = 0.032). Human Sgo1-downregulated tumours (tumour to normal mucosa ratio<0.5) had preferential location on the left side large bowel rather than on the right side (p = 0.012), and a higher variation of centromere numbers revealed by fluorescence in situ hybridisation (FISH). To assess the effects of hSgo1 downregulation, hSgo1 knockdown was performed by transfecting the diploid HCT116 cell line with a short hairpin RNA expression vector. hSgo1 knockdown cells proliferated slowly because of both G2 /M arrest and apoptosis (p<0.001), and markers of CIN in the form of aneuploidy (p<0.001) and micronuclei (p<0.005) were later observed in hSgo1 knockdown cells. Increased centrosome amplification (p<0.05), the presence of binucleated cells and mitotic catastrophes were also noted in hSgo1 knockdown cells. Conclusions: These findings suggest that hSgo1-downregulated colorectal cancers have a clinicopathological character of CIN, and hSgo1 downregulation leads to CIN in colorectal cancer cells.